Understanding the regulation of aspartate metabolism using a model based on measured kinetic parameters - Gilles Curien; Olivier Bastien; Mylène Robert‐Genthon; Athel Cornish‐Bowden; María Luz Cárdenas; Renaud Dumas (Molecular Systems Biology, 2009)
Abstract The aspartate‐derived amino‐acid pathway from plants is well suited for analysing the function of the allosteric network of interactions in branched pathways. For this purpose, a detailed kinetic model of the system in the plant model Arabidopsis was constructed on the basis of in vitro kinetic measurements. The data, assembled into a mathematical model, reproduce in vivo measurements and also provide non‐intuitive predictions. A crucial result is the identification of allosteric interactions whose function is not to couple demand and supply but to maintain a high independence between fluxes in competing pathways. In addition, the model shows that enzyme isoforms are not functionally redundant, because they contribute unequally to the flux and its regulation. Another result is the identification of the threonine concentration as the most sensitive variable in the system, suggesting a regulatory role for threonine at a higher level of integration.